The risk of injury associated with body checking among Pee Wee ice hockey players: an evaluation of Hockey Canada`s national body checking policy change - Black, A. M.; Hagel, B. E.; Palacios-Derflingher, L.; Schneider, K. J.; Emery, C. A. (British Journal of Sports Medicine, 2017)
Background In 2013, Hockey Canada introduced an evidence-informed policy change delaying the earliest age of introduction to body checking in ice hockey until Bantam (ages 13-14) nationwide.